ANALISIS HUKUM PERJANJIAN JOINT VENTURE SEBAGAI PERLINDUNGAN INVESTASI DI INDONESIA - Khalilah, Putri; Laela, Sofa (Postulat, 2024)
Foreign direct investment activities are often realised through the establisment of joint venture companies registered as Limited Liability Company (PT) legal entities and joint venture agreements become an important instrument in regulating the relationship between foreign and national investors. This research uses a literature research method through a normative juridical approach reviewed from the Civil Code (KUHPerdata), Law No. 25 of 2007 on Capital Investment, and Law No. 40 of 2007 on Limited Liability Companies that regulate the provisions of protection of foreign investment activities in Indonesia. The purpose of this research is to evaluate the legal protection for foreign investors and national investors as well as the role of joint venture agreements in providing legal certaintu in Indonesia. Such protection is important to ensure that investments do not harm either party and support sustainable economic growth in Indonesia. The results show that the Investment Law and the Limited Liability Company Law provide sufficient legal framework to protect investors through joint ventures. However, there are still gaps related to improving for better legal certainty of Joint venture in Indonesia.